Pengaruh Jenis Sumbu Dan Konsentrasi Nutrisi Terhadap Sawi Samhong (Brassica juncea L.) Dengan Hidroponik Sistem Sumbu - Sapto Wibowo (Paspalum: Jurnal Ilmiah Pertanian, 2021)
The wick system is a hydroponic by utilizing the principle of capillarity of nutrient solutions that are absorbed by plant roots through the wick. Flannelette is a material that has the best water absorption and can be used as a wick, another alternative is stove wick. The concentration of nutrients given to plants must also be in needs. Samhong mustard is a type of mustard in the same class as pakcoy. This study aims to determine the effect of the type of wick and nutrient concentration on plant height, number of leaves, and plant weight using hydroponic wick system. The research method was carried out using two independent variables, namely the type of wick consisting of flannelette (S1) and stove wick (S2), and the nutrients concentration consisting of N1 (1,000 ppm), N2 (1,200 ppm), and N3 (1,400 ppm). The measurements results were compared using the Anova two-factorial design test with a level of 5%, and if the results were significantly different, then continued with the BNJ test at a significant level of 5%. The results showed that there was an effect of using different types of wicks and nutrient concentrations on the measurement results of samhong mustard. Flannel wick (S1) has better effect than the stove wick (S2), and the concentration of N1 nutrients has better effect than the concentrations of N2 and N3, with average plant height is 27.9 cm, average number of leaves are 18.8 strands, and the average plant weight is 128.6 g.